Peran E-commerce terhadap Pengangguran, Kemiskinan, dan Lingkungan di Indonesia: Klasterisasi dan Analisis Jalur untuk Strategi Pembangunan Berkelanjutan - Kautsar, Syahrizal; Ridwansyah, Rizki Riza; Priscilla, Nindia (Seminar Nasional Official Statistics, 2025)
E-commerce has the potential to open new jobs and reveal poverty through digital entrepreneurship and expanding market access. However, there are other challenges such as the closure of old jobs, increasing greenhouse gas emissions and air pollution. This study aims to analyze the impact of e-commerce businesses on poverty, unemployment, and environment. This study uses data from 38 provinces in Indonesia in 2023 which includes the percentage of poor people, unemployment rates, and greenhouse gas emissions sourced from BPS, Sentinel-5P satellite imagery, and MERRA-2. The study results show that 38 provinces in Indonesia can be divided into four clusters with different criteria and problems on e-commerce, poverty, unemployment, and environment. In addition, this study shows that e-commerce can reduce poverty but has the potential to increase unemployment rates and reduce environmental quality. So that the right policy is needed so that e-commerce can be utilized to realize sustainable development.